Studies with a Preparation of Urokinase - Dubber, Anne H. C.; McNicol, G. P; Wilson, Patricia A.; Douglas, A. S (Thrombosis and Haemostasis, 1967)
The evidence presented in this paper shows that though less coagulative than urokinase (Leo), urokinase (Abbott), both in vitro and in vivo, has coagulant activity. Further, evidence has been presented that urokinase may accelerate platelet aggregation. While it is likely that the intense fibrinolytic activity which may be produced by intravenous administration of urokinase would largely cancel out the coagulative activity in vivo, these properties in theory could predispose to thrombosis or perhaps more particularly to rethrombosis during therapy with urokinase and it would clearly be desirable, if possible, to obtain a preparation free from such coagulative properties.